A Cd(ii) and Zn(ii) selective naphthyl based [2]rotaxane acts as an exclusive Zn(ii) sensor upon further functionalization with pyrene. Issue 1 (10th December 2020) - Bej, Somnath; Nandi, Mandira; Ghosh, Pradyut
Abstract : A new pyrene derived multi-functional [2]rotaxane is synthesized using click chemistry via Ni 2+ templating and π–π stacking interaction and it acts as a selectively responsive sensor for Zn 2+ ions. Abstract : A new multi-functional [2]rotaxane, ROTX, has been synthesized via a Cu(i ) catalysed azide–alkyne cycloaddition reaction between Ni(ii ) templated azide terminated pseudorotaxane composed of a naphthalene based heteroditopic wheel, NaphMC, and an alkyne terminated stopper. Subsequently, ROTX has been functionalized with pyrene moieties to develop a bifluorophoric [2]rotaxane, PYROTX, having naphthalene and pyrene moieties. Detailed characterization of these two rotaxanes is performed by utilizing several techniques such as ESI-MS, (1D and 2D) NMR, UV/Vis and PL studies. Comparative metal ion sensing studies of NaphMC (a fluorophoric cyclic receptor), ROTX ([2]rotaxane with a naphthyl fluorophore) and PYROTX ([2]rotaxane having naphthyl and pyrene fluorophores) have been performed to determine the effect of dimensionality/functionalization on the metal ion selectivity. Although NaphMC fails to discriminate between metal ions, ROTX serves as a selective sensor for Zn(ii ) and Cd(ii ). Importantly, PYROTX shows exclusive selectivity towards Zn(ii ) over various transition, alkali and alkaline earth metal ions including Cd(ii ).